The Effect of Indentation Angle of Koch Fractal Boundary on the Performance of Microstrip Antenna - P. Nageswara Rao; N. V. S. N. Sarma (International Journal of Antennas and Propagation)
The effect of indentation angle of Koch fractal boundary applied to a triangular patch on the resonant behavior and bandwidth is presented. It is shown that the resonant frequency can be controlled by changing the indentation angle of the boundary. With the experimental verification, it is established that for an indentation angle of 30∘ more bandwidth is obtained compared to conventional 60∘.